Experimental study to evaluate the generation of reverberant shear wave fields (R-SWF) in homogenous media - Flores G. (2020)
In this work, we study the conditions in which a reverberant field is created by varying the number and locations of multiple mechanical sources, and then fitting axial and lateral autocorrelation profiles to theoretical models. Numerical simulation showed that at least 60 incident plane waves were necessary to generate a R-SWF. The general trend is that by applying more incident waves, the coefficient of determination improves and the error decreases. We report a bias error lower than 6% in the mean shear wave speed (pmbCs). Phantom experiments showed a similar tendency. Moreover, we demonstrated that the creation of a R-SWF based on the superposition of incident plane waves was possible. At least three vibration sources located at the top of the phantom surface were necessary to measure an average pmbCs with an error less than 9%. © 2020 IEEE.